Biosynthesis and Antimicrobial Activity of Silver Nanoparticles from Murraya koenigii Ocimum teniflorum Chitin and Chitosan - B, Krishnaveni (International Journal of Pharmaceutical & Biological Archive, 2014)
Biosynthesis and Antimicrobial Activity of Silver Nanoparticles from Murraya koenigii Ocimum teniflorum Chitin and Chitosan